Accelerating ESD-induced gastric ulcer healing using a pH-responsive polyurethane/small intestinal submucosa hydrogel delivered by endoscopic catheter. Issue 1 (4th January 2021) - Zhao, Long-Mei; Gong, Mei; Wang, Rui; Yuan, Qi-Juan; Zhang, Yi; Pi, Jin-Kui; Lv, Xiu-He; Xie, Yan; Xie, Hui-Qi
Abstract: Endoscopic submucosal dissection (ESD) is the standard treatment for early-stage gastric cancer, but the large post-operative ulcers caused by ESD often lead to serious side effects. Post-ESD mucosal repair materials provide a new option for the treatment of post-ESD ulcers. In this study, we developed a polyurethane/small intestinal submucosa (PU/SIS) hydrogel and investigated its efficacy for accelerating ESD-induced ulcer healing in a canine model. PU/SIS hydrogel possessed great biocompatibility and distinctive pH-sensitive swelling properties and protected GES-1 cells from acid attack through forming a dense film in acidic conditions in vitro . Besides, PU/SIS gels present a strong bio-adhesion to gastric tissues under acidic conditions, thus ensuring the retention time of PU/SIS gels in vivo . In a canine model, PU/SIS hydrogel was easily delivered via endoscopy and adhered to the ulcer sites. PU/SIS hydrogel accelerated gastric ulcer healing at an early stage with more epithelium regeneration and slight inflammation. Our findings reveal PU/SIS hydrogel is a promising and attractive candidate for ESD-induced ulcer repair.